Finansiering av djurstall - Carlsson, Lars (2005)
I conducted this examinasions work because I want to find out how loan to farmes are working and more specific towards younger farmers. What you have to think about before you go to the bank and what the banks are thinking about lending money to farmers. This work is based on an investment plan propasal for 20 000 laying hens on a farm in the Kalmar area. The investment plan propasals have two diffrent alternetives, one farm on 25 hectares and one on 50 hectares. I have chosen this becouse I wanted to study how the diffrent sizes of farms are changing the banks thoughts about lending money. These investment plan propasals have included four banks with questionnaire and deep interview. During the meeting with diffrent banks I have made inqurie about lending money to farming companies. Most of the banks I have talked to did say it should not be at all unlikely to lend money to this project. The Ölandsbank thought that I have calculated with to little money to run the company. The Nordeabank thought that the calculation was too weak. The banks i have talked to says that the farmers need to describe their bussiness plans more and better before they contact the bank about lending money. Some farmes need to be better to sell their products. It is very important to have a good repayment solution today and the person behind the investment is very important.